Relationship of field and in vitro fertility of dairy bulls with sperm parameters, including DAG1 and SERPINA5 proteins - Zoca, Saulo Menegatti; Walker, Julie A.; Kline, Adalaide C.; Andrews, Taylor N.; Rich, Jerica J. J.; Epperson, Kaitlin M.; Drum, Jessica Nora; Ortega, M. Sofia; Cushman, Robert A.; Perry, George A. (Frontiers in Animal Science, 2023)
Sperm interacts with the female reproductive tract and oocyte through proteins, these cell-to-cell interactions may play a role in sperm fertility. For consideration of a protein as a potential marker of fertility, there must be variability expressed among animals. The proteins dystroglycan (DAG1) and plasma serine protease inhibitor (SERPINA5) have been reported to play a role in cell-to-cell interaction. Thus, the objectives of this study were to characterize DAG1 and SERPINA5 proteins localization and abundance variability on bovine sperm, and to investigate the relationship of DAG1 and SERPINA5 with field fertility (sire conception rate; SCR), in vitro embryo production (IVP), and sperm parameters. Dairy bulls (n=22) were classified as High-SCR (SCR>1.0) or Low-SCR (SCR<-4.0), and Good [blastocyst (BL) by Cleavage (CL) ratio (BL/CL)>39%] or Poor (BL/CL<38%) BL/CL. Sperm were evaluated for DAG1 and SERPINA5 immunolocalization, and concentration in two separate ejaculates. Variance between bulls compared to within bulls was evaluated with GLM procedure. Relationship of SCR and IVP classification on DAG1 and SERPINA5 concentrations, percentage of tail labeled for SERPINA5, SCR, sperm total and progressive motility, sperm plasma membrane integrity (PMI), CL, BL, and BL/CL were evaluated with GLIMMIX, also, correlation between these variables were evaluated. Both proteins were localized on the sperm head; however, SERPINA5 was also localized on the sperm tail. There was greater variance in concentration among bulls compared to within bull for DAG1 (P<0.0001; 69.4vs49.1, respectively) and SERPINA5 (P<0.0001; 325.8vs285.4, respectively). There was a positive correlation between concentration of DAG1 and SERPINA5 (P=0.01; r=0.54), and percentage of tail labeled for SERPINA5 was correlated with PMI (P=0.05; r=0.44). There was no relationship between SCR and IVP classifications and DAG1 (P≥0.55), SERPINA5 (P≥0.54), or percentage of sperm tail labeled for SERPINA5 (P≥0.22). In conclusion, DAG1 and SERPINA5 were localized to the sperm head, and tail (SERPINA5). Concentrations of DAG1 and SERPINA5 on the sperm head were correlated with each other. Percentage of tail labeled for SERPINA5 was correlated with sperm PMI; however, neither protein was associated with SCR or IVP. Thus, results indicate that DAG1 and SERPINA5 concentrations are not good fertility markers for bull sperm.